Weaving into the Mediascape: An Institutional Ethnography of NGO Media Activism in South Africa (Global Media Journal - German Edition, 2019)
Media Monitoring Africa (hereafter MMA), is a Johannesburg-based non-governmental organization (NGO) with the goals to increase media quality, refocus media ethics, foster media diversity, and advance media democracy. Via an institutional ethnography, conducted during six weeks of fieldwork, I take up MMA’s particular case to investigate how the NGO has become understood as “part” of the South African mediascape, rather than an auxiliary agent. Through participant observation of the NGO’s daily routines, in-depth interviews with MMA members and local media professionals, as well as textual analysis of organizational documents, I found that MMA has managed to weave into the organizational fabric of the South African mediascape. The ethnographic data reveals that MMA is commonly perceived as a necessary element of the South African mediascape—a status that moves beyond the often strictly interventionist role of activist NGOs. I argue that MMA has achieved this unique social position in the mediascape through four central organizational-activist practices: 1. consistent intervention on the same sets of issues; 2. activist innovation around the mode of their intervention(s); 3. multilateral activism (political economy, media policy, media content); and 4. successful curation of relationships with media stakeholders.
Keywords: media activism; media monitoring; non-governmental organizations; South African media; South African media system